Intratumoral delivery of PD-1/PD-L1 and CTLA-4 inhibitors for recurrent/refractory solid tumors: a proof-of-concept treatment strategy - Tan, Hongye; Shah, Noor Ul Huda; He, Bingjia; Liu, Tianrun; Li, Tianheng; Liu, Manting; Gu, Yingying; Zhi, Cheng; Ou, Yongqiong; Huang, Junhao; Li, Ming; Zuo, Shenghua; et al. (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) are a leading immunotherapy. However, their application has not universally translated into significant benefits. A substantial number of patients either show resistance or relapse post-initial response, which emphasizes the need for more sophisticated therapeutic approaches. The drug combination is one promising route. The cancer-immunity cycle reveals the anti-tumor immune-related rate limiting steps of tumors. Theoretically, focusing on different phases of the cancer-immunity cycle can enhance therapeutic results. However, combination therapy includes a higher risk of adverse effects, which demand careful consideration.MethodsIn this study, we combined programmed death-1 (PD-1)/ programmed death ligand-1 (PD-L1) and cytotoxic T Lymphocyte antigen 4 (CTLA-4) inhibitors with a reduced dosage but via an intra-tumor drug delivery strategy to treat recurrent/refractory (R/R) advanced solid tumors.ResultsHerein, we report four patients with favorable outcomes (complete response for more than 2 years). In our cases, most TRAEs are of grade 1-2.ConclusionIntratumoral co-delivery of PD-1/PD-L1 and CTLA-4 inhibitors with reduced dosage shows promising efficacy and safety in R/R advanced solid tumors. In addition to reducing drug-related adverse events, this technology has advantages in activating tumor immunity.Clinical Trial Registrationhttps://clinicaltrials.gov/, identifier: NCT03755739.